Courts and kids pursuing educational equity through the state courts - Rebell, Michael A. (Chicago, Ill. ; London : University of Chicago Press, 2009)
Over the past 35 years, federal courts have retreated from actively promoting school desegregation, while state courts have begun promoting the vision of educational equity. This is the first detailed analysis of why state courts have taken on this active role and how successful their efforts have been.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Educational equalization -- United States; Educational law and legislation -- United States; Discrimination in education -- Law and legislation -- United States; Education; United States of America, USA; Jurisprudence & general issues; Education law